Is additive manufacturing improving performance in Sports? A systematic review - Novak, J. I.; Novak, A. R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Sport is an industry that may benefit from the opportunities offered by additive manufacturing (AM), and the media has portrayed increasing adoption of the technology in sports products. This systematic review aimed to consolidate and interpret the available empirical evidence concerning applications of AM in sports following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) 2015. Four databases were searched within the date range of January 1984 to May 2019, using 28 broad and specific search phrases. This search resulted in 26 articles for analysis, the first appearing in 2010. Twelve sports in total were identified across the literature, with running/walking the most popular sport with ten articles (38%) investigating AM, followed by cycling with four articles (15%) and badminton with three articles (12%). Ten articles (38%) observed improvements in performance of products developed via AM compared to conventionally manufactured products, eight articles (31%) found a similar performance, and five articles (19%) found a lower performance. From a technical perspective, powder bed fusion technologies were the most utilized with 50% of articles using either selective laser sintering (SLS) or selective laser melting (SLM), although 52% of articles did not name the 3D printer used and 36% did not name any software used to design or optimize products. 3D scanning technology was also utilized in 11 articles (42%). Results indicate that AM has been slow to permeate sports research, and while considered across a variety of potential applications, has largely resulted in singular studies with potentially limited opportunities or funding for follow-up investigations.